FEATURES OF THE COMBINATION OF THYROID CANCER AND BACKGROUND DISEASES OF THYROID PARENCHEMA - Karachentsev Yu. I.; Dubovik V. M.; Gopkalova I. V.; Filonenko N. G.; Khaziev V. V.; Sokolova S. S.; Sazonov M. Е. (Вісник проблем біології і медицини, 2020)
Aim. The aim of this study was to evaluate the features and frequency of combinations various forms of thyroid cancer (TC) with background pathology of the thyroid parenchyma. Patients and methods. This was a retrospective study of 424 histological preparations of patients with TC who had undergone thyroidectomy over an 12-year period (between 2008 and 2019). Was determined of morphological variant of the TС, which appeared of combinations of with and without other pathology of the thyroid parenchyma. All statistical calculations were performed using Statistica 6.0. Copy right © Stat Soft, Inc. 1984-2001, Serial number 31415926535897. Statistical data processing was performed using Pearson χ2 test and Fisher’s exact test. Results. Of the 424 studied histological preparations of the thyroid gland, 178 were diagnosed with papillary carcinoma (PC), 161 had follicular carcinoma (FC), 50 had medullary carcinoma (MK), 25 had Gyurtle cell carcinoma (G-CLA), and 10 was poorly differentiated carcinoma (NDC). It has been shown that a large number of thyroid cancer develops against the background of benign thyroid pathology, most often against the background of colloid goiter (38%), autoimmune thyroiditis (29.5%) and follicular adenoma (26%), very few against of diffuse toxic goiter. (1.4%). Follicular adenoma of the thyroid gland is significantly more common in follicular carcinoma than in papillary and medullary carcinomas. As an independent disease, the studied carcinomas occurred in 35.8% of cases, and most often of them – follicular and medullary. Papillary thyroid cancer was most common against the background of autoimmune thyroiditis (47%) and colloid goiter (42%), less often with follicular adenoma (22%) and only in three cases with diffuse toxic goiter and only in combination with another background pathology. Follicular thyroid cancer with an equally high frequency occurred against the background of colloidal goiter and follicular adenoma (36 % and 35 %, respectively), significantly less frequently against the background of autoimmune thyroiditis (2.5 %) and diffuse toxic goiter (1.4 %). Gürtle cell carcinoma was most often found against the background of autoimmune thyroiditis and colloid goiter (48%), less with follicular adenoma (24 % of cases) and mainly with autoimmune thyroiditis and colloid goiter medullary cancer was detected with the same frequency with colloid goiter and autoimmune thyroiditis (28 %), and twice less often with follicular adenoma (14 %) and never with diffuse toxic goiter. Conclusions. The found high frequency and variety of pathological changes in the thyroid tissue against the background of various forms of cancer requires optimizing differential diagnosis, surgical tactics and strategy of postoperative treatment of this pathology.